Correção de fratura de crista tibial após avanço da tuberosidade tibial (TTA) com técnica de tta modificada - Prada, Tiago Carmagnani [UNESP]; Minto, Bruno Watanabe [UNESP]; Guiduce, Marcos Vinicius Sicca [UNESP]; Gianuzzi, Leandro Lira (Universidade Estadual de Londrina, 2015)
Corrective osteotomies are challenging techniques that require specialized training and acquisition of specific materials. Nevertheless, they have been increasingly studied and used in clinical routine in the world. Several variations on the model and the application technique have been developed and refined in search of the improvement of surgical techniques and development of implants more affordable to purchase. The tibial tuberosity advancement (TTA) consists on stabilization of tibial plateau perpendicular to the patellar tendon through the tibial tuberosity advancement. Our goal is to report a surgical complication of fracture of the tibial crest after TTA procedure. A dog with a confirmed diagnosis of rupture of the cranial cruciate ligament (CCLR) was operated using conventional technique of TTA. After 3 days of surgery, the same animal had a fracture of the proximal tibial crest. The animal was sent back to surgery and was used a variation of TTA technique, with autologous iliac wing and three cortical screws. This variation of the technique was able to replace the original technique successfully.
Tibial crest fracture correction after tibial tuberosity advancement (TTA) using a modified TTA technique
Keywords: Cranial cruciate ligament rupture; Knee; Osteotomies; Tibial plateau; TTA